Fund flows and performance in Brazil (2015)
This study analyzes how fund flows react to past performance in the dynamic Brazilian equity fund market over the period from 2001 to 2012. The study also tests for a “smart money” effect (Zheng, 1999), or whether funds that receive more money subsequently outperform those that receive less money. We find that investor flows chase past performance, and document some differences in the flow–performance relationship between retail and institutional funds. We do not find evidence of a “smart money” effect for the entire sample of funds. Nonetheless, flows in small and retail funds, which are often seen as populated by less sophisticated investors, do anticipate future fund performance.